The Impact of Practical Experiential Learning on Shaping High School Students' Attitudes Towards Biology - Apeadido, S.; Mensah, G. O.; Opoku-Mensah, D. (Universitas Negeri Yogyakarta, 2024)
The study explores the impact of experiential learning on students' attitudes in the biology classroom, addressing two primary research questions and corresponding hypotheses. Specifically, it examines how participation in practical biology work influences student attitudes and identifies the aspects of practical work with the greatest impact. The instruments underwent rigorous reliability and validity testing, achieving a Cronbach's alpha of 0.81 during field-pilot testing at a similar school. A convenience sample of 45 Form 2 General Science students from one class of Juaben Senior High School in Ghana was utilised, employing a one-group pre-test and post-test design. Data analysis used descriptive and inferential statistics, including paired samples t-tests, to evaluate attitude changes. Key findings reveal that participation in practical work significantly improves students' attitudes toward biology, with a notable increase in interest, understanding, and application of biological concepts. The aspects of practical work with the most significant impact include observation engagement and collaborative learning, both showing large effect sizes. These findings highlight the critical role of practical experiential learning in biology education, suggesting that integrating diverse and interactive practical activities into the curriculum can lead to improved student outcomes and a deeper appreciation for biology. The study recommends regular integration of practical activities in the curriculum, professional development for educators, fostering a supportive classroom environment, aligning with broader STEM initiatives, and advocating for policy changes prioritising experiential learning.